Perancangan UI/UX Sistem Penerimaan Mahasiswa Baru Berbasis Perangkat Mobile dengan Metode Design Thinking - Muhammad Jidan Narizki; R Arri Widyanto; Nugroho Agung Prabowo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The admission of new students is a crucial stage in the administrative process of higher education institutions. An efficient system and good User Interface/User Experience (UI/UX) design in the process of admitting new students are very important to create a positive academic environment. This study aims to design an optimal UI/UX on mobile device-based new student admissions systems at Muhamadiyah University of Magelang (UNIMMA). The method used is design thinking which includes analysis of user needs, problems, ideation, prototyping, and testing. The results of this study are the UI/UX design of the Unimma New Student Admissions (PMB) application based on mobile devices. The results of the tests conducted show that the design of the PMB UI/UX application using the design thinking method is able to improve the quality of the user experience in using the UNIMMA PMB application. This is evidenced by the results of usability testing which shows a significant increase in user satisfaction with the application. The test results use data based on user perceptions obtained through surveys, interviews and observations of prospective new students and related stakeholders. It is hoped that the results of this research will contribute to improving the efficiency and quality of the user experience in the UNIMMA new admissions system. This research can also provide guidance and reference for other tertiary institutions in designing a mobile device-based new admissions system with a design thinking approach.